2019
DOI: 10.26434/chemrxiv.8156702.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observation of dissipative chlorophyll-to-carotenoid energy transfer in light-harvesting complex II in membrane nanodiscs

Abstract: <pre><p><a></a>Green plants prevent photodamage under high light conditions by dissipating excess energy as heat. Conformational changes of the photosynthetic antenna complexes activate dissipation by leveraging the sensitivity of the photophysics of the chlorophyll and carotenoids to their surrounding protein. However, the mechanisms and site of dissipation are still debated, largely due to two challenges. First, because of the ultrafast timescales and large energy gaps involved, measu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Indeed, experimental and computational results suggest that LHCII explores several conformations in solution 17,32 . However, little is known about the behavior of the antenna in the photosynthetic membrane, which has been compared with the detergent environment only in recent experiments 26 . In order to understand the in vivo quenching mechanism of LHCII, the unquenched conformations of LHCII in the membrane need to be thoroughly characterized by a joint computational and experimental effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, experimental and computational results suggest that LHCII explores several conformations in solution 17,32 . However, little is known about the behavior of the antenna in the photosynthetic membrane, which has been compared with the detergent environment only in recent experiments 26 . In order to understand the in vivo quenching mechanism of LHCII, the unquenched conformations of LHCII in the membrane need to be thoroughly characterized by a joint computational and experimental effort.…”
Section: Discussionmentioning
confidence: 99%
“…In this contribution, we fill this gap, and show that electron transfer from carotenoids can be a rapid quenching pathway for excited Chl, and that it can compete with the EET to the S 1 state. To prove this hypothesis, we have focused on the major light-harvesting complex II (LCHII) of plants, for which previous studies have already shown the effectiveness of the EET mechanism 7,9,10,26 .…”
mentioning
confidence: 99%
“…This suggests the operation of a mechanism in which modulation of excitation quenching is rather realized in the thylakoid membranes indirectly, e.g. via the influence on a molecular organization of the pigment-protein complexes or by modifying their immediate environment (Ruban et al, 1997;Gruszecki et al, 2006;Johnson et al, 2011;Xu et al, 2015;Welc et al, 2016;Son et al, 2020b;Zhou et al, 2020). The results of the experiments have been presented, showing that both Zea (Ruban et al, 1997;Gruszecki et al, 2006;Zhou et al, 2020) and PsbS (Sacharz et al, 2017) influence molecular organization of LHCII.…”
Section: Analysis Of Light Intensity Profiles Of Zea Synthesis Withinmentioning
confidence: 99%
“…This shows that, Figure 7). In our opinion, it is highly probable that such a control of excitation quenching in LHCII is mechanistically realized via influencing the conformation and dynamics in the complex, directly associated with the photophysical processes, including excitation energy transfer to the S1 state of carotenoids (Son et al, 2020b;Son et al, 2020a). plants results in the increase of availability of Vio for enzymatic deepoxidation ( Figure 1A).…”
Section: Analysis Of Light Intensity Profiles Of Zea Synthesis Withinmentioning
confidence: 99%
See 1 more Smart Citation